Managing resources for futuristic wireless networks - Rath, Mamata (A volume in the Advances in wireless technologies and telecommunication (AWTT) book series, 2021)
"This book examines the issues, algorithms, and solutions for achieving best resource utilization in vehicular ad hoc networks" - Provided by publisher